KEPATUHAN WAJIB PAJAK UMKM : PERAN SANKSI PAJAK SEBAGAI MODERASI: MSME TAXPAYER COMPLIANCE: THE ROLE OF TAX SANCTIONS AS MODERATION - Riski Hernando; Fitrini Mansur; Eko Prasetyo (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2022)
This study examines the effect of understanding accounting, tax regulations, tax knowledge and tax sanctions on MSME taxpayer compliance. This study also explores the moderating effect of tax sanctions on the link between accounting expertise, tax knowledge, and MSME taxpayer compliance. The population uses MSMEs in Jambi City with a sample of MSMEs engaged in the food and beverage sector with specified criteria. Thus, the participants of this study amounted to 74 respondents. The research questionnaires were distributed using hand delivery systems and processed using SEM PLS (Warp PLS 7.0). The results of the study show a variety of findings where understanding accounting does not affect MSME taxpayer compliance in Jambi city. Understanding tax regulations and punishments might influence MSME taxpayers in Jambi directly or indirectly. This study's paradigm and analytical methods are fresh and enriching. This study's results contribute practically and theoretically, especially by the government, to MSME tax socialization.